The influence of Islam on the statecraft of the Perak sultanate: the case of the ninety-nine laws of Perak - Sulkafle, Mohamad Hazizie; Zakariya, Hafiz (Asian Scholars Network (ASNet), 2020)
This study examines the extent of Islamic influence on the Ninety-nine Laws of Perak. It adopts the legal-anthropological functional approach, which regards law as the means by which conflict and disputes are resolved in the society and as a system that operates in conjunction with other schemes to regulate and control the social order. It emphasizes that the traditional Malay laws, should be accepted as they are, instead of comparing them with the modern concept and definition of laws. Indeed, the Malay traditional laws functioned as the constitution of the Malay sultanates, which are workable and able to institute a modicum of social stability in a pluralistic and hierarchical society. Moreover, this set of laws served as a guide for the rulers and state officials to fullfil their responsibilities towards the sultanate and to the people.